Pelatihan Membuat E-Commerce Untuk Pemasaran Online Pada UMKM Akrilik - Devia Kartika; Rima Liana Gema; Erdisna Erdisna (Jurnal Pengabdian Masyarakat Dharma Andalas, 2022)
Community Service Activities in Micro, Small and Medium Enterprises (MSMEs) This Acrylic Village aims to conduct training on making Commerce help Independent Enterprises community in solving the problems they face in efforts to develop businesses, ranging from aspects of production and business management to especially in terms of digitalization-based marketing, which is expected to be will create economic independence and increase their business income. Special Targets in UMKN digitalization training activities and E-Commerce Development Training on making E-Commerce for Online marketing for MSMEs Acrylic and E-Commerce account creation will be held on June 6, 2022. Training and creation This e-commerce is aimed at SMEs in the acrylic village. ECommerce built in form of marketing in the form of a website. It is hoped that with the MSME digitization training and Making E-Commerce this will form a self-employed community innovative in the marketing process, Independent and responsive to market demands so that will make a positive contribution to society and the environment.